EXPLORATORY EFFECTS OF VOCATIONAL COUNSELLING STRATEGY AND GENDER ON CAREER AWARENESS OF IN-SCHOOL ADOLESCENTS IN GOMBE STATE, NIGERIA - Olanrewaju, MURAINA Kamilu (PUPIL: International Journal of Teaching, Education and Learning, 2018)
This study focused on exploratory effects of vocational counselling strategy and gender on career awareness of in-school adolescents in Gombe State, Nigeria. Pretest-posttest, control group quasi-experimental design with a 2x2 factorial matrix was used in the study. Multi-stage sampling technique was used in sampling 115 participants from 3 local government areas (12 schools) in the state. The respondents were measured with validated scale of 0.85 reliability coefficient and the data obtained was analyzed using T-test statistical analysis. Two (2) research hypotheses were formulated and tested at 0.05 level of significance. The results showed that there was significant difference in the career awareness of in-school adolescents exposed to vocational counselling strategy and those in the control group and there was significant difference in the career awareness of male and female in-school adolescents. In view of these findings, the study recommended that educational stakeholders should intensify their effort to organize seminars/conferences on the implications of vocational counselling strategy as effective interventions towards enhancing career awareness and that teachers should emphasis during their lesson, the career implications of subjects so that student will see how individual subjects relate to existing careers thus increasing their knowledge of occupations.